Meningkatkan Kebugaran Jasmani Menggunakan Permainan pada Siswa Kelas VI Sekolah Dasar Negeri 2 Pojok Kota kediri - Bima Kukuh Dwi Pamungkas; Moh. Nur Kholis; A. Zakiyyunnuhaa Fishilia (JOURNAL SAINS STUDENT RESEARCH, 2025)
Sports lessons are primarily part of the entire education system. The purpose of sports education is not only in the physical domain, but also aspects of health, physical form, skills for critical thinking, emotional stability, social skills, discussion, and ethical behavior through physical and sports activities. Sports lessons give students the opportunity to participate in a systematic, oriented, planned learning experience through physical activity, games and systematic movements. Based on the above explanation, the author conducted a study on improving the title of physical forms by relying on micro-class students to study physical education at Koljok 2 Elementary School in Kediri city. This research was conducted as educational research (Classic Action Research). The test results for February 19, 2025 after learning using the game approach, the results in cycle I for male students increased to 2.15 "while for female students increased to 2.21", while the results on February 26, 2025 in Cycle II male students increased to 2.12 "and female students increased to 2.17". Thus it can be concluded that students' abilities in mastering physical fitness learning materials through the pick kun move game approach and the police catch criminals can improve the physical fitness of grade VI students at Pojok 2 Elementary School, Kediri City with a 600 m running test.